2000
DOI: 10.4049/jimmunol.164.10.5019
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Human CytomegalovirusUL40Gene Product Contains a Ligand for HLA-E and Prevents NK Cell-Mediated Lysis

Abstract: Human CMV has evolved multiple strategies to interfere with immune recognition of the host. A variety of mechanisms target Ag presentation by MHC class I molecules resulting in a reduced class I cell-surface expression. This down-regulation of class I molecules is expected to trigger NK cytotoxicity, which would have to be counteracted by the virus to establish long-term infection. Here we describe that the human CMV open reading frame UL40 encodes a canonical ligand for HLA-E, identical with the HLA-Cw03 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
223
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(229 citation statements)
references
References 23 publications
4
223
2
Order By: Relevance
“…Similar results were obtained by co-transfection of UL40 and HLA-E in K562 cells. 24 More interestingly, Cerboni et al 25 have extended these results by showing how IFN-g can increase the inhibitory effect of UL40, through the upregulation of HLA-E. These findings may have important biological implications and support the hypothesis that IFN-g released during an antiviral or antitumoral response may lead to enhanced inhibitory signaling to effector cells carrying the CD94/NKG2A receptors and thereby turn off their effector functions.…”
Section: Discussionsupporting
confidence: 57%
“…Similar results were obtained by co-transfection of UL40 and HLA-E in K562 cells. 24 More interestingly, Cerboni et al 25 have extended these results by showing how IFN-g can increase the inhibitory effect of UL40, through the upregulation of HLA-E. These findings may have important biological implications and support the hypothesis that IFN-g released during an antiviral or antitumoral response may lead to enhanced inhibitory signaling to effector cells carrying the CD94/NKG2A receptors and thereby turn off their effector functions.…”
Section: Discussionsupporting
confidence: 57%
“…However, an HLA-E-binding peptide is contained within the leader sequence of HCMV gpUL40. We recently demonstrated that adenoviral expression of UL40 in cell lines induced TAPindependent up-regulation of HLA-E cell-surface expression (21) and elicited protection against lysis by NK cells (21,22). Recent data has suggested that this effect may be enhanced by IFN␥ (23), but no studies to date have investigated UL40 in the context of an active HCMV infection.…”
Section: Nk Cells ͉ Inhibitionmentioning
confidence: 99%
“…[122][123][124] In other cases, viral proteins that block NK cell activity interact with MHC-like molecules. The HCMV-specific UL16 protein interferes with the recognition of activating NKG2D receptors on NK cells by binding to MHC class I-related molecules such as MIC and ULBP, which serve as ligands for these activating receptors.…”
Section: Control Of Viral Immune Responses: Paralysis By Different Mementioning
confidence: 99%